Comparative study of gamma-irradiated PP and PE polyolefins part 1: Identification and quantification of radicals using electron paramagnetic resonance. (23rd October 2015) - Fel, Elie; Khrouz, Lhoussain; Massardier, Valérie; Bonneviot, Laurent
Abstract: Three grades of polypropylene (PP) and two grades of polyethylene (PE) were γ-irradiated with 25 kGy integral dose in air atmosphere and investigated using X-band electron paramagnetic resonance (EPR). All the spectra exhibited a mixture of free radicals, the absolute spin concentration of which was obtained from EPR signal simulations and intensity calibration using references of known spin concentrations. The free radicals were identified and their concentrations were related to both formulation and crystallinity of the polymer. The recombination of each species was monitored versus temperature. The concentration decay versus time concentration was monitored and simulated as a mixture of zero or first order mechanism for HDPE and of one for the PP polymers. In the highly crystalline High Density Polyethylene HDPE, γ-irradiation produces mainly alkyl radicals (R) and some alkyloxyl (RO) formed in low mobility phases where dioxygen has poor accessibility. Heating at 330 K destabilizes the alkyloxyl that disappears while allylic radicals (R–CHCH–CH2 ) show up as a fingerprint of β-scission. At 290 K in HDPE, the radical concentration decays rather rapidly according to a single exponential decay. A residual concentration of allyl and alkyl radicals (zero order mechanism) is assigned to radicals located in the largest crystallized zones of very weak molecular mobility. In contrast, low density PE or PP exhibit mostly oxidised radicals of alkylperoxyl (R–OO) type that are rather stable in PP (time constant τ ∼ 70 h), the decay of the non-oxydized part is much faster (τ ∼ 2 h) in PP. The higher concentration of radicals in PP than in HDPE (τ ∼ 8 h) is then attributed to the oxidised radicals while highly stable radicals (zero order mechanism) are consistent with a low density material. Graphical abstract: Highlights: In HDPE, γ-irradiation produces mainly alkyl radicals (R) and some alkyloxyl (RO) Residual concentration of allyl and alkyl radicals in the HDPE largest crystallized zones. Low density PE or PP exhibit mostly oxidised radicals of alkylperoxyl (R–OO) type. Simulation of EPR spectra.